Peran Kepala Sekolah dalam Meningkatkan Mutu Pendidikan Sekolah - Dwi Elok Kharismawati (Faculty of Education Universitas Negeri Malang, 2019)
Abstract: The objective of this study describes the role of the principal: (1) as a manager in improving the quality of education; (2) as a leader in improving the quality of education; and (3) supporting and inhibiting factors in improving the quality of education, and solutions to the constraints faced. The method used in this study is a qualitative approach with a type of case study research. Data collection techniques in this study were interviews, observation, and documentation. The results obtained from this study are: (1) the role of the principal as a manager in improving the quality of education is managing by doing planning, organizing, mobilizing, and evaluating; (2) the role of the principal as a leader in improving the quality of education is to monitor, mediate between teachers and students, discipline, motivate, innovate, liaise with outside parties, guide students in a sustainable manner, foster and improve teacher skills, and make decisions; and (3) supporting factors in improving the quality of education are the many relationships, support of the foundation, based on Islamic boarding schools and semi-modern nuances, students are free to choose, facilitate teachers; while the inhibiting factor is the collision of the system with service, frequent teacher turnover, certification policies, lack of awareness of school people, difficulty in implementing digital learning, team coordinators are not always available, data on foreign students, manual accounting, sometimes constrained by costs. Abstrak: Penelitian ini bertujuan untuk mendeskripsikan peran kepala sekolah: (1) sebagai manajer dalam meningkatkan mutu pendidikan; (2) sebagai pemimpin dalam meningkatkan mutu pendidikan; dan (3) faktor pendukung dan penghambat dalam meningkatkan mutu pendidikan, dan solusi pada faktor penghambat yang dihadapi. Metode yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan jenis penelitian studi kasus. Teknik pengumpulan data dalam penelitian ini adalah wawancara, observasi, dan dokumentasi. Hasil yang diperoleh dari penelitian ini adalah: (1) peran kepala sekolah sebagai manajer dalam meningkatkan mutu pendidikan adalah mengelola dengan melakukan perencanaan, pengorganisasian, penggerakkan, dan evaluasi; (2) peran kepala sekolah sebagai pemimpin dalam meningkatkan mutu pendidikan adalah memantau, menjadi perantara guru dan siswa, mendisiplinkan, memotivasi, membuat inovasi, penghubung dengan pihak luar, membimbing siswa secara berkelanjutan, membina dan meningkatkan kemampuan guru, dan membuat keputusan; dan (3) faktor pendukung dalam meningkatkan mutu pendidikan adalah banyaknya relasi, dukungan yayasan, berbasis pondok pesantren dan bernuansa semi modern, siswa bebas memilih, memfasilitasi guru; sedangkan faktor penghambat adalah berbenturan sistem dengan dinas, sering pergantian guru, kebijakan sertifikasi, kesadaran warga sekolah yang kurang, sulitnya penerapan digital learning, koordinator tim tidak selalu ada, data siswa luar negeri, menghitung keuangan secara manual, terkadang terkendala biaya.